Gene action, heterotic patterns, and inter-trait relationships of early maturing pro-vitamin a maize inbred lines and performance of Testcrosses under contrasting environments - Badu-Apraku, Baffour; Obisesan, O.; Olumide, O.B.; Toyinbo, J.O. (MDPI, 2021)
Vitamin A deficiency is the leading cause of night blindness, total blindness, maternal and childhood mortality in developing countries. Drought, low soil nitrogen and Striga hermonthica parasitism are major constraints to maize production in sub-Saharan Africa (SSA). Thus, the development of multiple stress tolerant maize varieties with elevated levels of PVA is an economically feasible approach to simultaneously tackle malnutrition and food insecurity in SSA. The objectives of this study were to determine the gene action modulating the inheritance of grain yield and other traits, group the inbred lines, investigate inter-trait relationships among grain yield and other traits and assess the performance and stability of single-cross hybrids derived from a set of inbred lines under stress and non-stress environments. One hundred and ninety diallel crosses plus six hybrid checks were evaluated under managed drought at Ikenne during the 2016/17 and 2017/18 dry seasons, low soil N conditions at Mokwa and Ile-Ife, Striga infestation at Abuja and Mokwa, and optimal management conditions at Ikenne, Kadawa, Abuja, Bagauda and Mokwa during the 2016 and 2017 growing seasons. Both additive and non-additive gene actions were prominent in the inheritance of grain yield and other measured traits under stress and optimal management conditions. However, additive gene action was preponderant over the non-additive. The PVA inbreds were classified into three heterotic groups with TZEI 25 and TZEIOR 164 identified as inbred testers for heterotic groups 2 and 3, respectively. Plant and ear heights, ears per plant, plant and ear aspects were identified as reliable secondary traits for genetic enhancement of grain yield under both stress and non-stress conditions. Hybrids TZEIOR 4 × TZEIOR 158 and TZEIOR 119 × TZEIOR 158 were outstanding in performance and should be tested extensively for possible commercialization to combat malnutrition and food insecurity in SSA.